EFFECT OF HOUSING SYSTEM, AGE AND HYBRID TYPE ON THE WELFARE OF LAYING HENS - MIRJANA DJUKIĆ-STOJČIĆ; LIDIJA PERIĆ; NIKO MILOŠEVIĆ (Scientific Papers Animal Science and Biotechnologies, 2023)
Housing system has a significant effect on the welfare of laying hens, and one of the factors for estimating the welfare is the condition of feathers. The aim of this work was to evaluate this parameter in different housing systems and between two strains (white and brown layers) at the beginning and ending of the production cycle. Feathers were evaluated by scoring system. Obtained results showed that type of the cage as well as the type of hybrid, have significant influence on feather.